PENYESUAIAN PERNIKAHAN DI BULAN MUHARRAM PADA PASANGAN BUGIS TELUK PAKEDAI, KUBURAYA - Aldy Yono Susanto; Agus Handini (The Institute for Research and Community Service (LP2M) of Pontianak State Institute of Islamic Studies (IAIN Pontianak), 2023)
This study aims to describe the adjustment of marriage in couples who marry in the month of Muharram, which actually includes the full month of prohibition or taboo. Data were collected in Teluk Pakedai, Bugis central area in Kuburaya, through observation, interview, and documentation. The informant consisted of couples who got married in the month of Muharram and traditional leaders. In conclusion, there are several Buginese couples in Teluk Pakedai who are abstinent, getting married in the month of Muharram. So far, however, there have been no problems in their marriage. This couple can make adjustments normally without obstacles or problems as the community believes. Overall, their adjustment to a partner, sexual adjustment, and financial adjustment went well. The study also showed that neither the parents, the couple's family nor the community showed a bad stigma to the object.